Political camerawork : documentary and the lasting impact of reenacting historical trauma - Rice, D. Andy (David Andy) (Indiana University Press, 2023)
"What mental and physical distress do actors, camerapersons, and reporters experience when working on reenactments of traumatic moments in history? In Political Camerawork, D. Andy Rice theorizes that the intense feelings produced while creating these performed scenarios, called "simulation documentaries," connect difficult pasts to the present. Building on his background as a nonfiction film director, producer, editor, and cinematographer, Rice analyzes performance techniques to gain insight into the emotional toll of simulation documentaries, including those reliving the Vietnam War, the US military's embodied training in California during the Iraq War, and an annual quadruple lynching reenactment organized by Black civil rights activists in Georgia. Investigating the lasting impact of these productions, Political Camerawork reveals that, by performing a simulation of a traumatic event they didn't directly experience, those involved become carriers of the trauma"--